Accumulated GABA activates presynaptic GABAB receptors and inhibits both excitatory and inhibitory synaptic transmission in rat midbrain periaqueductal gray. Issue 6 (12th April 2017) - Li, Guangying; Shao, Caifeng; Chen, Qian; Wang, Qiang; Yang, Kun
Abstract : γ-Aminobutyric acid (GABA), the major inhibitory neurotransmitter, activates ionotropic GABAA receptors and metabotropic GABAB receptors in the central nervous system, respectively. In ventrolateral division of the midbrain periaqueductal gray (PAG), GABAB receptors play important roles in pain modulation. However, the role of endogenous GABA action in presynaptic GABAB receptors remains elusive. Using whole-cell recordings on acute PAG slices from adult rats, here, we show that ambient GABA exerts a tonic inhibition on presynaptic terminals by binding GABAB receptors. Extracellular GABA accumulated by nipecotic acid, which blocks GABA transporters, strengthened GABAB receptor-mediated presynaptic inhibition on both excitatory and inhibitory synapses. Our results indicate that PAG neurons experience GABAB receptor-mediated inhibition determined by GABA transporters. The accumulated GABA-mediated actions may indicate a therapeutic way.